Effective Passivation of InGaAs Nanowires for Telecommunication Wavelength Optoelectronics. Issue 18 (28th June 2022) - Azimi, Zahra; Gopakumar, Aswani; Li, Li; Kremer, Felipe; Lockrey, Mark; Wibowo, Ary Anggara; Nguyen, Hieu T.; Tan, Hark Hoe; Jagadish, Chennupati; Wong‐Leung, Jennifer
Abstract: Catalyst‐free InGaAs nanowires are promising building blocks for optoelectronic devices operating at telecommunication wavelengths. Despite progress, the applications of InGaAs nanowires remain limited due to their high density of surface states that degrade their optical properties. Here, InGaAs nanowires with superior optical properties are achieved by effectively suppressing their surface states with an InP passivation shell. Optimal InP shell growth conditions and thickness to maximize the minority carrier lifetime are identified. The photoluminescence intensity of these passivated InGaAs nanowires is up to three orders of magnitude higher than that of their bare counterparts. Moreover, a long minority carrier lifetime of up to ≈13 ns is measured with these passivated nanowires at room temperature. Optimal passivation of InGaAs nanowires with an emission wavelength of 1530 nm results in an ultra‐low surface recombination velocity of ≈280 cm s −1 . In addition to the shell, the crystal structure of these nanowires plays an important role in the luminescence intensity. Combined cathodoluminescence mapping and high‐resolution transmission electron microscopy along the nanowires reveal significantly lower emission intensities in wurtzite predominant sections of the nanowires than zinc blende predominant ones.These insights on the optimal passivation of InGaAs provide directions for engineering high‐performance nanoscale‐devices in the telecommunication wavelength. Abstract : In this article, the engineering of InGaAs/InP core/shell nanowires with applications in telecommunication wavelength devices is reported. By carefully controlling the growth of an InP shell, the surface recombination velocity can be significantly decreased, resulting in a record‐high lifetime of 13 ns at the emission wavelength of 1.53 µm.